Reciprocal Questioning Procedures in Reading Comprehension: Does It Increase Students’ Motivation? - Bq Zuhrotun Nafisah; Dedi Sumarsono (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
Reading is essential and serves as a basic building block in English language learning process. As a result, a teacher must have an effective teaching technique in teaching reading comprehension. This study aims to find out the influence of reciprocal questioning towards students’ motivation in reading comprehension of the third-grade students at SMP Negeri 3 Praya. The research was conducted through experimental research, the pre-test and post-test were used as the design. The instrument was used a set of questionnaires (Likert scale) for motivation test. The data analysis that used was descriptive analysis and inferential analysis for measuring the motivation test in form of questionnaires. Then, according to the result of the test, it showed that t-test 4.865 was higher than the t-table 2.423 at the level of significance 0.50. It means that, there was a positive effect of Reciprocal Questioning procedure towards students’ motivation in reading comprehension.